Problem Based Learning: Supporting Active Student Responding in Writing - Wijayatiningsih, Testiana Deni; Lestariningsih, Enny Dwi (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Students had difficulties to focus and got the idea to write their research report when they asked to finish their writing in certain time.Therefore, the researchers conducted the research on applying Problem Based learning (PBL) to support the Active Student Responding (ASR) in writing. Theobjectives of this research is to describe the studentsresponses in writing academic research especially their final project. The subjects of this study are the eighth semester of Universitas Terbuka who join Pemantapan Kemampuan Profesional subjects. The research methodology is descriptive quantitative.The sampling technique of the research is simple random sampling which uses 20 students from the eighth semester. The data obtained from questionnaire and observation.The reserach study concludes that the application of Problem Based Learning (PBL) encourage students to be creative in writing and enhance studentscritical thinking in solve theproblem. They tend to have a big effort to finish writing on their final project. It can be seen from the means result of studentsconcept learning questionnaire 69.8%. It meant that there were a big motivation from the students to write their research project.